Congenital Junctional Ectopic Tachycardia in a 6-month-old boy treated with Ivabradine: A Case Report - Upreti, Dinesh; Shakya, Samir; Gajurel, Ratna Mani; Shrestha, Hemant; Thapa, Sanjeev; Sharma, Manju (Nepalese Heart Journal, 2023)
Congenital junctional ectopic tachycardia (JET) is a rare tachyarrhythmia found in young infants and is often difficult to treat. JET is characterized by incessant tachycardia which causes ventricular dysfunction, heart failure and high mortality. Ivabradine is one of the newer antiarrhythmic drugs with special indications in decreasing heart rate in adults with chronic heart failure. It has shown promising role in congenital JET. However, there are no guidelines recommending ivabradine as a first-line agent for congenital JET. We report an infant with congenital JET who was successfully treated with ivabradine.